THE CORRELATION BETWEEN SMOKING BEHAVIOUR AND THE BODY MASS INDEX IN RELATION TO THE INCIDENCE OF KNEE OSTEOARTHRITIS IN THE ELDERLY, UTILIZING THE WESTERN ONTARIO AND MASTER INDEX - Alvin Abdillah; Agus Priyanto; Dian Muslimah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Osteoarthritis is a progressive condition affecting the joints, where there is an accumulation of cellular stress, breakdown of the extracellular matrix, and gradual deterioration of the articular cartilage. This leads to the bones rubbing against each other, causing pain, stiffness, and impaired mobility. The Kwanyar Community Health Center documented a total of 194 instances of knee osteoarthritis between July and September 2022. The objective of this research is to examine the correlation between body mass index and smoking habits, as well as the occurrence of knee osteoarthritis in older individuals, using the Western Ontario and McMaster index. The study design employs analytics using a cross-sectional methodology. The survey had a total of 86 participants. There were 54 responders from whom samples were obtained. The sample approach employs probability sampling with the Simple Random sample technique. The data collecting method employs a questionnaire form. The statistical analysis employs the Spearman Rank test with a significance level of 0.05. The ethical testing of this study has been conducted by the KEPK STIKes Ngudia Husada Madura team. The study findings indicate that the analysis is conducted using the Spearman Rank statistical test, yielding a significant result (p=0.000) which is lower than the significance level (a=0.05). It may be inferred that there is a correlation between body mass index and smoking habits in connection to the occurrence of knee osteoarthritis in older individuals, as measured by the Western Ontario and McMaster index. For the aged, it is advisable to enhance their body mass index and modify their smoking habit as a preventive measure against knee osteoarthritis. The study aims to investigate the correlation between the respondents' understanding of body mass index and smoking habits, and the occurrence of knee osteoarthritis in older individuals.